Habitat filtering drives the local distribution of congeneric species in a Brazilian white‐sand flooded tropical forest. Issue 4 (17th January 2021) - Ribeiro, Kelly F. O.; Martins, Valéria F.; Wiegand, Thorsten; Santos, Flavio A. M.
Abstract: The investigation of ecological processes that maintain species coexistence is revealing in naturally disturbed environments such as the white‐sand tropical forest, which is subject to periodic flooding that might pose strong habitat filtering to tree species. Congeneric species are a good model to investigate the relative importance of ecological processes that maintain high species diversity because they tend to exploit the same limiting resources and/or have similar tolerance limits to the same environmental conditions due to their close phylogenetic relationship. We aim to find evidence for the action and relative importance of different processes hypothesized to maintain species coexistence in a white‐sand flooded forest in Brazil, taking advantage of data on the detailed spatial structure of populations of congeneric species. Individuals of three Myrcia species were tagged, mapped, and measured for diameter at soil height in a 1‐ha plot. We also sampled seven environmental variables in the plot. We employed several spatial point process models to investigate the possible action of habitat filtering, interspecific competition, and dispersal limitation. Habitat filtering was the most important process driving the local distribution of the three Myrcia species, as they showed associations, albeit of different strength, to environmental variables related to flooding. We did not detect spatial patterns, such as spatial segregation and smaller size of nearby neighbors, that would be consistent with interspecific competition among the three congeneric species and other co‐occurring species. Even though congeners were spatially independent, they responded to differences in the environment. Last, dispersal limitation only led to spatial associations of different size classes for one of the species. Given that white‐sand flooded forests are highly threatened in Brazil, the preservation of their different habitats is of utmost importance to the maintenance of high species richness, as flooding drives the distribution of species in the community. Abstract : We aim to find evidence for the action and relative importance of different ecological processes hypothesized to maintain species coexistence in a tropical forest subject to seasonal flooding, using the spatial structure of populations of three congeneric species. We collected environmental data and data on trees of three Myrcia species within a 1‐ha plot of a Brazilian white‐sand flooded tropical forest. We find that habitat filtering to areas subject to flooding is the most important ecological process driving the local distribution of the species studied in a white‐sand forest.